Visible-light-promoted selective O-alkylation of 2-pyridones with α-aryldiazoacetates. Issue 2 (16th December 2020) - Yang, Jingya; Wang, Ganggang; Zhou, Hongyan; Li, Zhifeng; Ma, Ben; Song, Menghui; Sun, Rongxia; Huo, Congde
Abstract : Under direct blue light irradiation, the selective O -alkylation of 2-pyridones with α-aryldiazoacetates has been achieved. Abstract : A visible-light-promoted O–H insertion reaction between 2-pyridones and α-aryldiazoacetates has been developed. Upon visible light irradiation, the reaction proceeds smoothly under mild and catalyst-free conditions. A wide scope of 2-pyridones and α-aryldiazoacetates are well tolerated, and various O -alkylated 2-pyridones are obtained with perfect selectivity and good functional group tolerance. A photoinduced radical process is probably responsible for the excellent selectivity.